Pemanfaatan Internet of Things (IoT) Dalam Sektor Pertanian Oleh Petugas Pertanian Di Kecamatan Pamijahan, Bogor: Internet of Things (IoT) Utilization in the Agricultural Sector by Agricultural Officers in Pamijahan, Bogor - Windihastuty, Wiwin (KRESNA: Jurnal Riset dan Pengabdian Masyarakat, 2021)
The rapid development of communication technology produces communication media that can be used to disseminate information. One of the communication media that can be used is the internet. The internet is one form of the use of communication technology. Agricultural instructors as agro-industry information disseminators are required to be able to take advantage of the development of communication technology in carrying out their duties and functions in disseminating agro-industry information. The purpose of this study is to describe the use of the internet by agricultural extension workers, to analyze the factors that influence the analysis of the use of information and its relationship to the level of its use. Utilization of information by agricultural officers as a necessity which will then be shared with fellow officers for discussion. The results of the interviews, the level of use of the internet as a medium of communication is still low. This is known to be due to the lack of knowledge of farmers about the function of the internet as a communication medium. Based on this, so that farmers can use the internet as a communication medium, it is necessary to receive guidance and counseling from agricultural sector officers.